Testing the nutrient value of chicken manure in the decomposition of Trichoderma viride - Siti Hardianti Wahyuni; Dini Puspita Yanti Nst (Jurnal Pertanian Tropik, 2018)
Testing the macro nutrient value of chicken manure decomposed by Trichoderma viride. This study aims to determine the value of macro nutrients in chicken manure decomposed by Trichoderma viride. This research was carried out on the field of the Faculty of Agriculture, Graha Nusantara Padangsidimpuan University, from February to August 2018. The results showed that compost with the addition of decomposer Trichoderma viride which was good was 4 weeks (A4), namely organic B = 45.70%, organic C = 91.03, C / N ratio = 11, 13%, total N = 3.51%, total P = 3.41%, total K = 1.58%